'Do not talk to strangers': A study on trust in Brazilian ridesharing apps. (November 2020) - Vaclavik, Marcia Cristiane; Macke, Janaina; Faturi e Silva, Daniel
Abstract: The emergence of digital platforms based on network algorithms can mediate relationships of trust, boosting sharing economy business models. This study aims to identify the motivations and trust elements of ridesharing apps and analyze the weight of motivation variables in the explanation of trust in the platform service. The survey method was applied to a sample of 485 Brazilian users of a ridesharing app were addressed. Five factors were analyzed to users' motivation: Perceived sustainability, Security risks, Enjoyment, Platform quality, and Economic reward. Results show that 50.6% of respondents use the service until three times per month (n = 246), while 12, 6% use more than four times per week. This study contributes by showing that: (i) five key user motives and two types of trusts are empirically measured and examined for the Brazilian ridesharing market; (ii) the most significant variable that explains trust in platform is "Information providing", following by platform safety and platform security; (iii) pleasant participation, enjoyment, and cheaper alternative were also significant for the trust in the platform; and (iv) trust in platform is higher than trust in drivers. These contributions could enhance applied solutions for sharing economy platforms and guide academic research on the topic. Highlights: Five key user motives and two types of trusts are empirically measured and examined for the Brazilian ridesharing market. Five factors (economic reward, sustainability, enjoyment, quality, safety risk) are related to trust (platform and drivers) These five factors explain 73.80% of the motivations of users of ridesharing applications. The immediate benefits to the users are fundamental for the formation of trust and adhesion to the sharing economy. Users tend to value more the technological aspect (trust in the platform) than the human aspect (trust in drivers).